Trends of the anthropogenic CO2 along 20ºW in the Iberian basin - Fajar, Noelia; Pardo, Paula C.; Carracedo, L.; Vázquez Rodríguez, Marcos; Ríos, Aida F.; Pérez, Fiz F. (Universidad Autónoma de Baja California, 2012)
10 páginas, 7 figuras, 3 tablas The carbon system in the water masses of the Iberian basin (North Atlantic Ocean) has been affected over the last two decades by the raise of the anthropogenic CO2 (Cant). In order to study the storage of Cant in the Iberian basin, the variables of the carbonic system were measured among others [i.e., pH, total inorganic carbon (CT) and total alkalinity (AT)] during the CAIBOX cruise. This cruise, conducted between July and August 2009 on board “B/O Sarmiento de Gamboa”, was included on CAIBEX project (Shelf–ocean exchanges in the Canary–Iberian Large Marine Ecosystem). The storages of Cant were estimated using two different back-calculation techniques (i.e., method and TrOCA method) and for six layers of the water column corresponding to the approximate locations of the characteristic water masses of the region and layers of water masses mixing. For the whole water column and for the year 2009 the storages of Cant were of 88.1±3.8 and 93.7±3.7 molC∙m-2 from and TrOCA methods, respectively. Moreover, the Cant storage rate from 1993 to 2009 was also estimated considering data from three additional cruises (OACES 1993, CHAOS 1998 and OACES 2003). The determined Cant storage rates were 1.41±0.25 and 1.67±0.13 molC∙m-2∙y-1 for and TrOCA methods, respectively. The increase of anthropogenic CO2 uptake by the ocean can be seen when comparing these results with Ríos et al. (2001). Between the periods 1977-1997 and 1993-2009, the Cant concentration increased around 28-49 % in the first 2000m. Part of the data presented in this paper has been obtained by means of CAIBEX Project: Shelf-ocean exchanges in the Canary-Iberia Large Marine Ecosystem (CTM2007-66408-C02/MAR), supported by the Spanish Council of Education and Science. The first author is funded by a predoctoral fellowship of the program JAE “Junta para la Ampliación de Estudios” from the Consejo Superior de Investigaciones Científicas (CSIC). Peer reviewed